Intelligent Control Using Metaheuristic Optimization for Buck-Boost Converter - P. Chanjira; S. Tunyasrirut (Journal of Engineering)
This research aims to introduce an intelligent controlling system of windmill-generated voltage connected to a load of 12 V. As natural wind speed lacks consistency, the resultant irregular voltage can lead to system damage. In the experiment, a buck-boost converter is not only designed to control such voltage but also tuned by intelligent methods. It is very challenging to control the system. PI controller is developed using metaheuristic optimization, an artificial fish-swarm algorithm (AFSA). In testing, the buck-boost converter is controlled by the PI controller at a reference voltage of 14 V and supplied with an input voltage Vin in the range of 5–100V. The result shows that, even with inconstant Vin, the system can effectively control the reference voltage at 14 V.